New possibilities for the treatment of systemic lupus erythematosus. How much does the effect cost? - E. A. Pyadushkina; A. M. Lila; E. E. Yagnenkova; V. I. Ignatyeva; E. V. Derkach (Современная ревматология)
Our previous study has shown that the new biologic disease-modifying antirheumatic drug (bDMARD) anifrolumab (AFM) can be considered as a cost-effective alternative to belimumab (BLM) in the treatment of systemic lupus erythematosus (SLE). Following a review by the Commission of the Ministry of Health of Russia, AFM was recommended for inclusion in the List of vital and Essential Drugs (VED).Objective: to conduct a clinical and economic analysis (CEA) of the use of bDMARD for the treatment of adult patients with moderate to severe SLE, to update the previously conducted CEA considering changing circumstances, including populational changes, price characteristics and law in the context of the Russian healthcare system, and to assess the impact of changes.Material and methods. The CEA was conducted from a healthcare system perspective and was based on the results of an indirect comparison of the efficacy of AFM and BLM drugs using a cost-effectiveness analysis. The costs of drug therapy with the compared bDMARDs for one year, the cost-effectiveness ratio and the incremental indicator of cost-effectiveness growth were calculated. Drug prices were calculated based on the register of maximum retail prices for drugs from the VED. A comparison of the main results of the analysis is presented.Results and discussion. The results of the indirect comparison of efficacy showed statistically significant advantages of AFM over BLM according to the SRI-4 criterion: odds ratio – 2.61 (95% confidence interval 1.22–5.58). The cost of therapy for one patient for 52 weeks, recalculated considering the changed indicators, for AFM in combination with standard therapy was 655.5 thousand rubles, for BLM – 622 thousand rubles, the difference in cost was 5.1%. When prescribing AFM, the cost of the effect (achieving a response to therapy according to the SRI-4 criterion) in one patient was 1181 thousand rubles, which is 38.6% lower than when using BLM (1924 thousand rubles). The additional cost of achieving a response according to SRI-4 in one additional patient for AFM compared to BLM amounted to 144 thousand rubles, which is significantly less than the previously calculated similar indicator – 3.4 million rubles.Conclusion. The CEA, considering the current data allows us to conclude that the use of AFM in patients with moderate to severe SLE is economically feasible within the framework of the Russian healthcare system. The expansion of the VED list by including new, more effective and economically justifiable options, and registration of maximum retail prices will increase the availability of SLE therapy, reduce the financial burden on the budgets of regions of the Russian Federation and enable more patients to receive the necessary treatment.